TREND TERKINI PENGAJARAN BAHASA DI PERGURUAN TINGGI: SATU ANALISIS - Mahamod, Zamri (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
This paper discusses the most current trend in language learning.Â It focuses on pedagogical content knowledge (PCK) which should be mastered by every langauge teachers.Â PCK refers to the knowledge of curriculum, curriculum content, teaching pedagogy, and studentsâ characters.Â Language teachers need to consider considerable changes in language education especially dealing with educational curriculum and language teachersâ trainings, language skills, the competence in teaching the suitable form and structure curriculum, teaching and learning strategies